2017
DOI: 10.1016/j.carbon.2017.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of carbonization conditions of polyaniline on its catalytic activity towards ORR. Some insights about the nature of the active sites

Abstract: N-doped carbon materials were obtained using polyaniline (PANI) as precursor. Heat treatment of PANI and de-doped PANI (PANId) was performed using different temperatures-600 and 800 ºC-. Two different atmospheres were used during the treatment: an inert atmosphere (N 2) and another one consisting on a slightly oxidizing mixture of gases (3000 ppm O 2 in N 2). The prepared materials at 800 ºC showed high values of capacitance, up to 170 and 255 F g-1 in basic and acid electrolytes, respectively, in spite of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
57
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 52 publications
(62 reference statements)
5
57
0
Order By: Relevance
“…Comparison of Figure 3a,b at the same area before and after annealing, shows that the overall shape of the nanofibers is retained; however, both the width and the height of PANI nanofibers are significantly reduced to about 50% after annealing (Figure 3c). This is consistent with previous reports that PANI undergoes dehydrogenation and cross-linking of adjacent chains upon high temperature pyrolysis, and that the weight of polyacetylene (PA) films/fibers [49][50][51] and PANI films/tubes [52][53][54][55][56][57][58] is reduced after pyrolysis while retaining the fibril morphology. I-V characteristics of the PANI nanofibers on G/SiC electrodes before annealing show that the adjacent G/SiC leads are electrically connected due to the PANI nanofibers contacting the two adjacent G/SiC electrodes.…”
Section: Characterization Of Graphene-nanofiber Devices Before and Afsupporting
confidence: 93%
See 2 more Smart Citations
“…Comparison of Figure 3a,b at the same area before and after annealing, shows that the overall shape of the nanofibers is retained; however, both the width and the height of PANI nanofibers are significantly reduced to about 50% after annealing (Figure 3c). This is consistent with previous reports that PANI undergoes dehydrogenation and cross-linking of adjacent chains upon high temperature pyrolysis, and that the weight of polyacetylene (PA) films/fibers [49][50][51] and PANI films/tubes [52][53][54][55][56][57][58] is reduced after pyrolysis while retaining the fibril morphology. I-V characteristics of the PANI nanofibers on G/SiC electrodes before annealing show that the adjacent G/SiC leads are electrically connected due to the PANI nanofibers contacting the two adjacent G/SiC electrodes.…”
Section: Characterization Of Graphene-nanofiber Devices Before and Afsupporting
confidence: 93%
“…In the pristine form, the Raman spectra of PANI nanofibers show complex peaks that indicates PANI nanofibers. Raman spectroscopy on the annealed PANI nanofiber bundles shows that the PANI nanofibers become amorphous carbon nanofibers as confirmed by the broad D (1353 cm −1 ) and G bands (1590 cm −1 ) of graphite (Figure 4b) [49][50][51][52][53][54][55][56][57][58][59]. In contrast, the G/SiC remained intact after annealing as shown in Figure 4b.…”
Section: Characterization Of Graphene-nanofiber Devices Before and Afmentioning
confidence: 85%
See 1 more Smart Citation
“…Moreover, experimental studies suggest that edge-type graphitic nitrogen 14,15 and pyrrolic nitrogen species 16,17 can also act as active sites. In recent years, N-C-O species 18,19 have also been proposed as active sites towards ORR due to the large positive charge density of the C atom adjacent to N and O atoms.…”
Section: Introductionmentioning
confidence: 99%
“…In the conventional way, PANI is prepared by aniline monomer, 1 m HCl, and APS under stirring, which leads to the formation of irregular particulates . Quilez‐Bermejo et al reported the synthesis of PANI using the above‐mentioned method, followed by heat treatment of PANI at different temperatures . Two different atmospheres were used during the treatment: an inert atmosphere of N 2 and another one consisting of a slightly oxidizing mixture of gases (3000 ppm O 2 in N 2 ).…”
Section: Doped Nanocarbons From Panimentioning
confidence: 99%